Forest decompositions of graphs with cyclomatic number 2 - E. J. Farrell (International Journal of Mathematics and Mathematical Sciences)
The tree polynomials [1] of the basic graphs with cyclomatic number 2 are derived. From these polynomials, results about forest decompositions are deduced. Explicit formulae are given for the number of decompositions of the basic graphs into forest with specified finite cardinalities.